On the association of lightning activity and projected change in climate over the Indian sub-continent - Saha, Upal; Siingh, Devendraa; Kamara, A.K.; Galanaki, Elissavet; Animesh, Maitra; Singh, R.P.; Singh, A.K.; Chakraborty, Swastika; Singh, Rajesh (My University, 2017)
The association of lightning activity with the long-term as well as seasonal spatio-temporal distribution of convective available potential energy (CAPE), surface convective precipitation, vegetation cover and anthropogenic aerosol loading over the Indian sub-continent has been studied for the period 2000–2014. The north-east to north-west arc including the foothills of the Himalayas is the primary seats of lightning occurrences. The correlations of lightning activity with each of aerosol loading, vegetation cover, convective instability and convective precipitation helps us in understanding the definite entity that is responsible for changing the lightning activity in different parts of this tropical region. Lightning flash rate (LFR) has significant positive correlations (r ~0.5–0.7) with AOD, CAPE and surface convective precipitation but significant negative correlation (r ~−0.4)with Normalized Difference Vegetation Index (NDVI). Using global circulation models from the Climate Model Intercomparison Project Phase 5 (CMIP5), time-series of observed and projected upper tropospheric water vapor, surface convective precipitation and aerosol optical depth (AOD) from the historical simulations (1996–2005) and RCP8.5 emission scenario (2036–2045) are analyzed over the Indian region that are vulnerable to climate change in terms of occurrence of convective events and associated hazardous lightning phenomena. This study indicates that upper troposphericwater vapor (300 hPa) has a significant linkage with the lightning occurrences associated with convective activities and strong updraft. During the mid- 21st century, AOD, surface convective precipitation and specific humidity are projected to increase by 1.42%, 2.01% and 1.40%, respectively which may result in regional changes in lightning activity over the Indian sub-continent.
Keywords: Aerosols; Climate change; Lightning; CAPE; NDVI; CMIP5; Normalized Difference Vegetation Index; Climate Model Intercomparison Project Phase 5; Convective available potential energy